Stand density and productivity of sainfoin - S. A. Ignatiev; A. A. Regidin; N. S. Kravchenko; K. N. Goryunov (Зерновое хозяйство России)
Prolonged vegetation and changes in weather and climatic conditions according to seasons and vegetation periods result in the loss of sainfoin plants and a decrease in productivity of forage and seeds. The identification of new varieties with high adaptability to the agroclimatic conditions of a particular region of their cultivation, the study of patterns of changes in various economic traits according to a year of life will allow selecting more productive and adapted lines and forms of sainfoin plants. The purpose of current paper was to present the study of plant density of sainfoin varieties and new lines during 3 years of life according to their productivity. The study was carried out in the laboratory for breeding and seed production of perennial grasses of the FSBSI Agricultural Research Center «Donskoy». The objects of study in the nursery for preliminary variety testing were 3 varieties and 6 lines of sandy sainfoin that were promising for feed and seed productivity. Conditions in the south of the Rostov region made it possible to obtain seedlings with a plant density of 309–313 pcs/m2 with a field seed germination rate of 75.2–80.2 %. In the second year of sowing, the plant stand density varied from 198 pcs/m2 to 251 pcs/m2. With such plant density there has been formed a dry mass yield of 6.41–7.17 t/ha. In the third year, the plant density compared to the previous year decreased significantly and varied from 109 pcs/m2 to 127 pcs/m2, while the dry mass yield was formed at 6.25–7.13 t/ha. The number of gen erative shoots in the studied varieties and lines varied over the years from 981 pcs/m2 to 1244 pcs/m2 in the second year, while the seed productivity of the best lines was 0.90–0.95 t/ha, and from 415 pcs/m2 to 525 pcs/m2 in the third year of life, while the best lines had a seed yield of 0.85–1.09 t/ha.